PKM PENDAMPINGAN SOSIALISASI PENDIDIKAN ANTI PERUNDUNGAN DI SDN SIWALAN KOTA SEMARANG - Ikha Listyarini; Listyarini, Ikha; Henry Januar Saputra; Kiswoyo; Moh Aniq Khairul Basyar (Kanigara, 2025)
Anti-bullying education, or education against bullying, has emerged as an important field aimed at addressing bullying behavior in various educational settings. Based on this, it is important to conduct anti- bullying outreach for young children in elementary schools. This is necessary because of the rampant cases of bullying occurring among adolescents, as published in various mass media. Another reason underlying the importance of holding anti-bullying outreach is that it can be an alternative preventative measure for adolescents to avoid falling into bullying cases. The goal of this community service is to help elementary school-aged children recognize the dangers of bullying for themselves and their friends. Furthermore, the method of implementing the community service is in several stages, namely anti-bullying education outreach for elementary school level, anti-bullying education outreach for junior high school level, and anti-bullying education outreach for high school level.